A stochastic assessment of the public health risks of fluoroquinolone resistance Campylobacter and the use of the drug in broiler production in Japan - Toyofuku, H.; Makita, K.; Osada, Y.; Ohashi, T.; Kakinuma, M.; Oushiki, D. (2015)
Purpose: Antimicrobial resistance (AMR) is a major global public health and a food safety issue. Risk analysis is an essential tool in assessing the risk to human health from foodborne AMR microorganisms and determining appropriate risk management strategies to control those risks. Although quantitative risk assessments are encouraged and have been performed in some EU countries and the US, so far only qualitative risk assessments are performed in Japan. This project was commissioned by the Japan Food Safety Commission in the context of its programme to develop a quantitative risk assessment, with Campylobacter in broiler and use of fluoroquinolone (FQ) for broiler production as an example. Methods: The risk assessment model was subdivided into the release, exposure, and consequence assessment sections. In the release section, FQ resistance mechanism and data from Japanese Veterinary Antimicrobial Resistance Monitoring Program were utilized for the model development. The model output was percentage of FQ resistance Campylobacter (FRC) among broiler borne human campylobacteriosis. In order to take uncertainties in the data into account, the model was built, and simulations were performed using @Risk 4.5 (Palisade Corp.) . Results: The average percentage of broilers infected with FRC was estimated to be 34.0%. Among FRC strains, 10.4% carried a mutation at Thr86Ile of gyrA with overexpression producing strains of efflux pump, 20.8% carried a same mutation of gyrA with low expression producing strains of efflux pump, and 2.8% carried a mutation of GyrA other places than Thr86Ile. The estimated that an average and the maximum annual number of Campylobacter infections per person were 1.02, and 88 times, respectively. Conclusions: In the maximum (88 infections per year) scenario, the patient is estimated to be infected with FRC 30 times, and 28 times out of 30 times, he or she is estimated to be infected with Campylobacter with a mutation of Thr86Ile of GyrA. Relevance: By using this model, use of FQ in the farm and the effect on the percentage of FRC in broilers was not identified. We couldn't find any adverse human health effects associated with FRC strains.